Transient effects of transfusion and feeding advances (volumetric and caloric) on necrotizing enterocolitis development: A case-crossover study. - Vi T Le; Mark A Klebanoff; Maria M Talavera; Jonathan L Slaughter (PLoS ONE)
Objective To evaluate the short-term effects of feed fortification, feed volume increase, and PRBC transfusion on the odds of developing NEC. Study design Case-crossover study of neonatal intensive care infants born at ≤ 32 weeks' gestation who were admitted to 5 central Ohio intensive care units from January 2012-July 2016 and developed NEC Bell Stage ≥2. Each patient served as their own control, with exposure during the 48-hour period just prior to NEC onset (hazard period) being compared to a preceding 48-hour control period, thus eliminating confounding by patient factors fixed between both intervals. NEC onset was determined by chart review as the earliest occurrence of one of the following within 24 hours of confirmatory x-ray: (1) antibiotic initiation, (2) enteral feeding cessation, (3) physician first notified of abdominal concerns, or (4) abdominal x-ray ordered. Conditional logistic regression compared exposures to feed volume increase, fortification, and PRBC transfusion during the 48-hour period prior to NEC onset to those during a preceding 48-hour control period. Analyses were stratified by gestational age and anemia (defined: hemoglobin ≤ 9.3 g/dL within 7 days of NEC onset). Results We included 63 infants with confirmed NEC. Acute exposure to fortification (odds ratio [OR]: 1.67, 95% confidence interval [CI]: 0.61, 4.59), feed volume increase (OR: 0.63, 95% CI: 0.28, 1.38), and PRBC transfusion (OR: 1.80, 95% CI: 0.60, 5.37) was not associated with the onset of NEC. Gestational age and anemia did not significantly modify the associations. Sensitivity testing substituting 24- and 72-hour hazard and control periods produced similar results. Conclusion Using a case-crossover design, we did not detect an association between NEC development and feed fortification, feed volume increase, or PRBC transfusion within 48-hours prior to NEC-onset. Replication in a larger set of cases is needed.